SOCIAL NETWORKS IN PERSONNEL MARKETING - Bokenchina L.K.; Bokenchin Kazbek. K. (Academic Journal of Physical and Chemical Sciences, 2020)
With modern options of social media it is essential to use all the options available for hiring purposes. The companies evolve and hiring professionals becomes harder especially in current low unemployment in Europe, or especially the Czech Republic. This thesis focuses on various options of social media and analyses them in order to evaluate the knowledge about such options among workers on one hand and maximize possible utility for the companies in order to find the best professionals on the other hand. The goal is to specify the benefits of social media for human relations marketing and hiring. An important outcome will thus be a set of recommendations to be used in an HR agency. The analytical part is divided into two subparts where the first one focuses on semistructured interviews with recruiting specialists and the second subpart discusses the results of a questionnaire distributed among job applicants. The key result of the thesis is that an online strategy for hiring must be always finely defined and combined with other hiring methods.